2022
DOI: 10.1002/cmdc.202200425
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Small Sets of Molecules for Synthesis throughin‐silicoTools: A Comparison of Common Ranking Methods

Abstract: Prioritizing molecules for synthesis is a key role of computational methods within medicinal chemistry. Multiple tools exist for ranking molecules, from the cheap and popular molecular docking methods to more computationally expensive molecular‐dynamics (MD)‐based methods. It is often questioned whether the accuracy of the more rigorous methods justifies the higher computational cost and associated calculation time. Here, we compared the performance on ranking the binding of small molecules for seven scoring f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 119 publications
0
37
0
Order By: Relevance
“…Additionally, a blind molecular docking was performed to assess the potential binding of each control compound at the site predicted by the DoGSiteScorer tool (assigning a docking score) [ 28 ]. In this study, blind molecular docking showed docking scores of −9.2 to −7.1 Kcal/mol of the control compounds at the Lm TIM dimer interface ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a blind molecular docking was performed to assess the potential binding of each control compound at the site predicted by the DoGSiteScorer tool (assigning a docking score) [ 28 ]. In this study, blind molecular docking showed docking scores of −9.2 to −7.1 Kcal/mol of the control compounds at the Lm TIM dimer interface ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, more validation methods need to be used jointly for a better prediction. Molecular dynamics-based methods, although computationally expensive, are reported to perform better in ranking molecules compared with docking methods including ChemPLP, AutoDock Vina and Glide [ 23 ]. For example, top ranking molecules selected by a PLP fitness score could be further screened by molecular dynamics-based methods before inhibitor purchasing for experimental verification.…”
Section: Discussionmentioning
confidence: 99%
“…This reinforces conclusions in an earlier paper by Hou et al [ 69 ]. Other reports suggest that MM/PBSA binding energies were better for ranking than docking scoring functions [ 70 ], while others have shown no significant difference [ 71 ], with both being less effective than MD alchemical methods. Our prior studies on repurposing drugs active against SARS-CoV-2 enzyme targets also established a strong correlation between MM/PBSA energies and those calculated from a thermodynamic cycle [ 9 , 11 ].…”
Section: Methodsmentioning
confidence: 99%